Increasing people's knowledge about HIV/AIDS: an investigation into the effectiveness of reading as a communication strategy (2009)
among the factors probably causing stigma and discrimination against people living with /Human IMMunodeficiency Virus (HIV)/ Acquired Immune Deficiency Syndrome (AIDS) (PLWHA) are the public's inadequate knowlegde and strong misconceptions about the pandemic. Having realised this fact, stakeholders intensify efforts at educating the public about HIV/AIDS. Reading is one of the communication strategies they employ to enrich people's knowledge about the disease. This article, therefore, focused on reading, primarily to investigate its effectiveness as a receptive communication skill, through which the public can be better educated about HIVAIDS and thus, dispel their misconceptions about the disease and its patients. An experimenta method was employed, using 220 respondents. Two separate instruments- attitude scale/questionnaire and an HIV/AIDS- related story- were used. The result showed that abosolute majority of respondents (78.2 per cent) from the experimental group, which actually read the select HIV/AIDS- related story demostrate better knowledge about HIV/AIDS than do the respondents from the control group. Thus, the study has established reading as an effective communication strategy for educating people and dispelling their misconceptions about HIV/AIDS and its patients. The findings also showed that there is a statistically significant difference in the attitude of male and female subjects to HIV/AIDS and PLWHA after reading the story.